STUDI TENTANG HUBUNGAN PENGETAHUAN TERHADAP DETEKSI DINI KANKER LEHER RAHIM DI KAWASAN PESISIR DAN KEPULAUAN AMBALAU - Mayasari, Windatania (NHM PRESS, 2024)
Ca Cervix at the fourth rank from all of oncology in women in the word after ca mamae, colorectum and lungs. Early detection uses the IVA method. Data in 2021, from 390 women in fertile age who have early detection amounted to 60 women (15%). This research determined to relate knowledge with ca cervix early detection with IVA method in coastal and islands area at 2023. This research used analysis description with cross sectional study. 78 women in fertile age as respondents of this research. Instrument of this research used a questionnaire. Data processing used SPSS with chi square test. Results of chi square got relationship knowledge with early detection cancer cerviks equal 0,000 p<0,05). Conclusion of this research showed there was relationship between knowledge to ca cervix in coastal and islands area at 2023.